PENGARUH PERMAINAN PERMATA TERSEMBUNYI TERHADAP KEMAMPUAN MENGENAL WARNA ANAK USIA 4-5 TAHUN DI TK ASH-SHOFA SUNGAI SEGAJAH KECAMATAN KUBU KABUPATEN ROKAN HILIR - Sukariah, Sukariah; Indarto, Wusono; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The ability to know the color of children aged 4-5 years in kindergarten Shofa Ash River District Segajah Kubu not be separated from the problems that occurred. One of the problem is the color identifier can not achieve maximum results in line with expectations of teacher as well as the objectives of the implemetation of learning . one of which is the teachers have never been applying game hidden gem.Keywords: Games Hidden Gem, About Color